Algebraic Type Approximation to the Blasius Velocity Profile. (24th March 2014) - Yun, Beong In
Abstract : For the Blasius velocity profile we propose a simple algebraic type approximate function which is uniformly accurate over the whole region. Moreover, for further improvement a correction method based on a weight function is introduced. The availability of the proposed method is shown by the result of numerical experiments.